Numerical development of heat transfer correlation in asymmetrically heated turbulent channel flow. (January 2021) - David, Martin; Toutant, Adrien; Bataille, Françoise
Highlights: A review of heat transfer correlations for tube and channel ows is proposed. 3 correlations of the literature are evaluated in asymmetric heating conditions. Large Eddy Simulations at low Mach number in anisothermal channel are performed. A new heat transfer correlation for turbulent channel ows is investigated. A term accounting for asymmetric conditions is assessed in the correlation. Abstract: This study deals with forced convective heat transfer. It is divided into two parts. Firstly, a review of heat transfer involving forced convection in tubes and channels is proposed. In the case of channel geometry, studies dealing with symmetrically and asymmetrically heated flows as well as one side heated flows are reported. Then, a new correlation for symmetrically and asymmetrically heated channels associated with a turbulent flow is developed using Large Eddy Simulations. The Proposed Correlation, also referred to as PC, involves a specific term to handle asymmetric conditions. The domain covered by simulations is the following: heat fluxes vary between 4 and 580 kW/m 2, Prandtl number ranges from 0.76 to 3.18 and bulk Reynolds number from 10 600 to 177 000. Three correlations of the literature are compared to the one proposed in this paper. The conventional expressions tend to overestimate the Nusselt number at the hot side of asymmetrically heated channel independently of the temperature ratio. They, also, underestimate the heat transfer at the cold side, especially when the bulk temperature is close to the cold wall temperature. The proposed correlation provides great results in both heating conditions. The global accuracy associated with each correlation is quantified.